Factors associated with the use of sexual and reproductive health services by adolescents and youth in 2022,Cotonou, Benin - AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU; Damien Barikissou, Georgia (My University, 2022)
Introduction: In West Africa, young people are vulnerable to various sexual and reproductive health (SRH) problems such as unwanted pregnancy, HIV or other sexually transmitted infections (STIs) and unsafe abortion. The objective of this study was to measure the level of use of SRH services by adolescents and youth and the factors associated with it in the city of Cotonou in 2022. Methods: This was a descriptive, analytical cross-sectional study of a sample of 318 adolescents and youth and 21 health centres offering SRH services, randomly selected in the community by three-stage cluster sampling. Results: In the study population, 78.9% of young people had at least secondary education. Their overall level of good utilization of sexual and reproductive health services was assessed at 33.6%. Of the 21 health centers, 85.7% made their sexual and reproductive health services accessible to youth and only 28.6% offered abortion care. Good use of sexual and reproductive health services was more common among youth with a history of voluntary interruption of pregnancy (p = 0.013) or rape (p = 0.003). The risk of good sexual and reproductive health service use increased twofold when the youth had good sexual and reproductive health knowledge and ninefold when the youth had good sexual and reproductive health practice with OR (95% ) = 9.68 [3.99-23.48]. Conclusion: Promoting the use of SRH services among youth is critical to reducing the health problems they face.
Keywords: service utilization; sexual and reproductive health; youth; Cotonou.